The Impact of Television Media Efficiency on Contributor Journalists: A Case Study of News-Program Reduction in the Digital Disruption Era (Oratio Directa, 2025)
This study examines the impact of efficiency policies in the television industry on contributor journalists, focusing on news-program reduction in the era of digital disruption. It uses a qualitative case-study approach, with data collected through semi-structured interviews, participant observation, and documentation concerning efficiency policies and contributor contracts. Participants were contributor journalists working for national television media affected by news-program reduction. The findings indicate reduced working hours and income, greater social uncertainty, and declining media-worker welfare. Contributors developed survival strategies by expanding their digital-media and social-media skills. Workforce reduction also affected news-coverage quality. The study highlights the need to balance operational efficiency, worker welfare, and sustainable journalism quality, and recommends further research on journalists' digital adaptation amid technological disruption.
Keywords: Efficiency; Television media; News-program reduction; Digital disruption; Contributor journalists